Using item response theory to investigate the structure of anticipated affect: do self-reports about future affective reactions conform to typical or maximal models? - Zampetakis, Leonidas A.; Lerakis, Manolis; Kafetsios, Konstantinos; Moustakis, Vassilis (Frontiers in Psychology, 2015)
In the present research we used item response theory (IRT) to examine whether effective predictions (anticipated affect) conforms to a typical (i.e., what people usually do) or a maximal behavior process (i.e., what people can do). The former, correspond to non-monotonic ideal point IRT models whereas the latter correspond to monotonic dominance IRT models. A convenience, cross-sectional student sample (N=1624) was used. Participants were asked to report on anticipated positive and negative affect around a hypothetical event (emotions surrounding the start of a new business). We carried out analysis comparing Graded Response Model (GRM), a dominance IRT model, against Generalized Graded Unfolding Model (GGUM), an unfolding IRT model. We found that the GRM provided a better fit to the data. Findings suggest that the self-report responses to anticipated affect conform to dominance response process (i.e. maximal behavior). The paper also discusses implications for a growing literature on anticipated affect.